Cryptocurrency Prospect in the International Market: Pre-sent Value Management and Islamic Perspective - Ilham, Rico Nur; Arliansyah, Arliansyah; Juanda, Reza; Sinta, Irada; Ramansyah, Frengki Putra; Multazam, Muhammad (Malikussaleh University, Aceh, Indonesia, 2025)
Cryptocurrency is an investment commodity that can generate returns and already has a license to trade in exchange. This study aims to examine the prospects of digital cryptocurrency assets more deeply by summarising the results of literature studies in various countries. As a result of this study, it is known that many countries whose governments make strict regulations on support for legality and allow cryptocurrency transactions include: European Union members, namely Germany and Italy, and non-member countries of the European Union, such as Gibraltar. Furthermore, in the Americas, there are Canada and Venezuela. In East Asia and the Asia Pacific, Australia and Japan support the existence of Cryptocurrency. Meanwhile, in Southeast Asian countries, there are contradictions between several countries, including Indonesia, Malaysia, Vietnam, and the Philippines, that reject cryptocurrency transactions because they are considered threats to money laundering and the problem of terrorism. Of course, this is a prospect that cryptocurrency transactions can meet the expectations of all users in the world by making regulations regarding the legality of Cryptocurrency so that the transaction model can be integrated between users, both as an asset and a substitute for international payment currencies.